Dear Abolition: For Uncle Ralph - Purifoy, Danielle (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
In the wake of her uncle’s 2021 death from COVID-19 in a Michigan prison, Danielle Purifoy reflects on what his life and art taught her about abolition, and what kind of place could have given him a different life…and death.